Formative aspects of PANOS - Palcos novos palavras novas: a foreign, initial and exploratory look (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article analyzes formative aspects of the PANOS – Palcos novos palavras novas, developed by the National Theatre Dona Maria II in Lisbon, Portugal, which establishes intersections with school and youth theatre and new dramaturgies. Based on the finding that youth theatre is a field to be expanded and made visible within Brazilian and Portuguese theatrical studies, the authors reflect on working with written text, the role of the teacher-director in the articulation of contemporary dramaturgy and scene, and advocate for an expanded view of the field of Pedagogy of Theater Arts. A theoretical review carried out, readings of dramaturgy from the PANOS, interviews and observation in loco showed: gaps in artistic and educational investigations focused on youth in Portugal; challenges that a project like PANOS faces and raises; and, above all, its relevance for expanding the actions of reading, creating and appreciating theater and dramatic literature among youth.
Keywords: pedagogy of performing arts; contemporary dramaturgy in Portuguese; youth theatre; school